Sistemas transcurrentes de escala litosférica en el sur del Perú - Sempere, Thierry (2004)
[ENG] Three large transcurrent systems, with related magmatism, are identified in southern Peru. A ∼40-80km-wide, N150-trending, dextral corridor (CECLLA =Cusco-Lagunillas-Laraqueri-Abaroa structural corridor) is characterized by thick Oligocene basic lavas and numerous intrusions. The other two systems are oriented ∼N125-130 and sinistral, and cartographically related to the CECLLA. Miocene to Quaternary basic magmas are associated to the northeastern system (SFUACC = Urcos-Ayaviri-Copacabana-Coniri fault system). In the southwestern region, the abundant Late Cretaceous-Paleocene arc magmatism seems related to the Incapuquio-El Castillo fault system (SFIEC).